A comprehensive stochastic energy management system in reconfigurable microgrids. (12th April 2016) - Golshannavaz, Sajjad; Afsharnia, Saeed; Siano, Pierluigi
Summary: This paper addresses the joint stochastic energy and reserve scheduling problem in microgrids (MGs). The established approach proposes a novel high‐performance energy management system (EMS) making use of automatically controlled switches (ACSs). Accordingly, besides the optimal scheduling of active elements namely distributed generations (DGs) and responsive loads (RLs), the optimal topology of the network for each of the scheduling intervals is determined as well. Likewise, the effects of the reconfiguration process in probable variations of the scheduled energy patterns in DGs, RLs, and grid purchases are thoroughly assessed to highlight the alterations in unallocated capacities of these resources. Moreover, the uncertainties associated with both the load and wind speed forecasting errors are suitably accommodated through the reserve allocations. The proposed optimization procedure is formulated as a mixed‐integer non‐linear problem and resolved using a genetic algorithm (GA). The effectiveness of the projected framework is verified utilizing a typical MG, and the obtained numerical results are discussed in depth. Copyright © 2016 John Wiley & Sons, Ltd. Key findings: ‐ Devising an efficient EMS for optimal daily operational scheduling of emergent MGs; ‐ Joint stochastic energy and reserve scheduling for suitable accommodation of uncertainties; ‐ Incorporating flexible network topologies by ACSs in enhancing the economical and technical metrics; ‐ Considering the practical switching costs and limitations of ACSs to reach in a realistic scheme; ‐ Utilizing the unallocated capacities released by hourly reconfigurations as the potent reserve capacities.